Regulation of DEAH/RHA Helicases by G-Patch Proteins. (27th January 2015) - Robert-Paganin, Julien; Réty, Stéphane; Leulliot, Nicolas
Abstract : RNA helicases from the DEAH/RHA family are present in all the processes of RNA metabolism. The function of two helicases from this family, Prp2 and Prp43, is regulated by protein partners containing a G-patch domain. The G-patch is a glycine-rich domain discovered by sequence alignment, involved in protein-protein and protein-nucleic acid interaction. Although it has been shown to stimulate the helicase's enzymatic activities, the precise role of the G-patch domain remains unclear. The role of G-patch proteins in the regulation of Prp43 activity has been studied in the two biological processes in which it is involved: splicing and ribosome biogenesis. Depending on the pathway, the activity of Prp43 is modulated by different G-patch proteins. A particular feature of the structure of DEAH/RHA helicases revealed by the Prp43 structure is the OB-fold domain in C-terminal part. The OB-fold has been shown to be a platform responsible for the interaction with G-patch proteins and RNA. Though there is still no structural data on the G-patch domain, in the current model, the interaction between the helicase, the G-patch protein, and RNA leads to a cooperative binding of RNA and conformational changes of the helicase.